Aikido and randori reconciliation of two opposing forces - Allbright, Scott (Crowood Press, 2002)
Aikido is a defensive martial art that uses throws and joint locks. Tomiki Kenji, the founder of Shodokan Aikido, introduced randori, or freestyle format, into Aikido practice. This book sets out to explain the need for and scope of randori in Aikido practice. It explains the historical and philosophical principles behind randori, and the physiological principles of Aikido; ilustrates fundamental training and practice methods; describes the role of kata and randori in Aikido practice; and guides the player through the shodokan system and the grading syllabus. With over 300 illustrations, it is an essential learning aid for all Aikido students.